Memory and ethnicity : ethnic museums in Israel and the Diaspora - Trevisan Semi, Emanuela; Miccoli, Dario; Parfitt, Tudor (Cambridge Scholars Publishing, 2013)
In recent times, ethnicity and issues of origin have become a hotly debated topic among Jews both in Israel and in the Diaspora. This is particularly true both of Jews from the Middle East and North Africa, who for years had remained at the margins of the Israeli national narrative, as well as the Israeli Palestinian minority. Much the same may be said of Diaspora Jews. Among the public spaces where ethnicity has become more visible are museums, together with heritage centres, art galleries ...